Problems and prospects of fish nursery operators in Jessore district of Bangladesh - Halim, Md Abdul; Haque, Syed Ariful; Islam, Md Ariful; Sharmin, Mst Sonia; Rayhan, Abu (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A study was conducted to know the problems and prospects fish nursery operators in Jessore district. A total of 50 nursery operators (Jessore sadar, Jikhorgasha and Avynagor) were interviewed using a structured questionnaire during March-May 2016. The objective of the survey was to study different aspects on pond area, fingerling rearing status, nursery layer, number of employees, sources of fingerlings, survival rate, fingerlings prices, market system, capital sources, fingerling production, prospects and problems for nursery operators. In survey areas, most of the nursery operators were continued their business in two to five ponds with an average area of 1.25±0.04 ha. In the present study, it was found that 4.5±3.25 persons were associated in each nursery but the permanent manpower was minimal. The total fingerlings production in the selected nurseries were 1685 laks of where silver carp 23.74%, Rohu 20.77%, Catla 19%, Mrigal 14.84%, Common carp 10.68%, Koi 2.97%, Thai Puti 5.93%, Grass Carp 1.19% and Pangus 0.89%.The survival rate were 70-80%. Average price of Indian major carps- were Tk. 350 to 500, Chinese carp were Tk. 200 to 400, Thai sharpunti were 350-400 and Pungus were Tk. 400-500 fingerlings/ kg. In the study area, nursery operators were faced various problems such as lack of capital (21.25%), diseases problem (19.75%), high lease value (15.00%), shortage of water (5.00%), high price of production inputs (11.00%), flooding (3.00%), terrorism (11.00%), high temperature (3.00%), intense market competition (6.00%) and the lack of policy support (5.00%). Government should take proper care for nursery operators and fish associated communities for the enhancement of fishery production. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 429-434